Probing Majorana and Andreev bound states with waiting times. (28th November 2016) - Chevallier, D.; Albert, M.; Devillard, P.
Abstract: We consider a biased normal-superconducting junction with various types of superconductivity. Depending on the class of superconductivity, a Majorana bound state may appear at the interface. We show that this has important consequences on the statistical distribution of time delays between detection of consecutive electrons flowing out of such an interface, namely the waiting time distribution. Therefore, this quantity is shown to be a clear fingerprint of Majorana bound-state physics and may be considered as an experimental signature of its presence.